Problematika Asuransi Syariah (Takaful) di Indonesia - Handayani, Novia Putri; Widiastuti, Dina; Anwar, Agustian; Zahara, Anzu Elvia (Jayapangus Press, 2023)
This study aims to conduct a literature review of the results of previous studies related to Islamic insurance. The approach used in this study is a qualitative approach with a descriptive-analytical method. The results of the discussion explain that there are various problems that hinder the development of Islamic insurance in Indonesia. The results of the study concluded that there are factors causing delays in the development of Islamic insurance in Indonesia; there is a negative stigma attached to society due to the lack of responsiveness of the government; the lack of literacy and the pros and cons of halal is due to the lack of socialization, management and marketing strategy of sharia insurance which is less competitive than conventional insurance. This study recommends that the sharia financial institution industry which has previously developed rapidly such as banking can partner with sharia insurance institutions to jointly improve and develop their potential in conducting socialization, product marketing and the Islamic financial literacy movement.